(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
Based on the Analytic Hierarchy Process (AHP), a comprehensive evaluation system has been developed to assess the performance of vertical slot fishways. This system incorporates 30 factors related to fish passing efficiency, thereby facilitating a detailed analysis of hydraulic characteristics, engineering layout, operation management, and monitoring. For its practical application, the vertical slot fishway at the Laolongkou Hydro-junction project’s comprehensive evaluation was assessed and consequently rated as "Operating Excellently". This rating accurately reflects the fishway’s operational status. The case study demonstrates that the established index system and the model calculation method are capable of thoroughly considering the operational conditions of fishways and the applicability of the model. Moreover, the methodology offers valuable experiences and guidance for creating evaluation systems in various other water conservancy project sectors.